Readings in finance - Wolf, Harold A.; Richardson, Lee. (New York : Appleton-Century-Crofts, 1966)
It discusses the principles of finance, its financial analysis and capital budgeting.
Includes bibliographical references.
occ 16/01/2019
Loans
Keywords: Finance; Corporations